Refleksje na temat zdrowej i szczęśliwej starości w Żywocie człowieka poczciwego Mikołaja Reja i Zielniku Stefana Falimirza (sfery sacrum i profanum) - Adamczewska, Klaudia (Starość i młodość w literaturze i kulturze, 2016)
Mikołaj Rej and Stefan Falimirz took in their works the subject of old age, presenting it in two differentways. Falimirz wrote in herbarium about a sphere physicality, while Rej in the Life of an Honest Manof the spiritual sphere. The purpose of the human earthly journey is to achieve eternal life. This will bepossible if an entity full of site attempt to live according to Christian deeds. I wrote an article about thecombination of these two aspects.